A critical discourse analysis of PPSMI in Malaysian news media / Kiew Sieh Ping - Kiew, Sieh Ping (2012)
This research report seeks to realise and compare the different ideologies that are contained in reports from Malaysian mainstream and alternative media with respect to the issue of teaching science and mathematics in English (otherwise known by the Bahasa Malaysia acronym, PPSMI). More specifically, the study focuses on the discourse that centres around the government’s decision to abolish the PPSMI. To do so, the study analyses a corpus of 21 news reports from The Star and 13 from Malaysiakini. These reports span a period of three months, i.e. from June to August 2009. The media plays an important role in mediating texts and discourse. Therefore, it is important to realise the ideology behind each media house, as this ideology is disseminated and perpetuated within its news reports. By realising the ideology of the media house, the public can make an educated decision about what they read and evaluate the information they receive. In addition, the issue of PPSMI is critical as education policies affect the next generation, who will be the country’s future leaders. Critical Discourse Analysis (CDA) is the most helpful framework for examining and uncovering the ideology embedded in texts and discourse. Therefore, using Norman Fairclough’s (2001) three-dimensional framework, the study will conduct an intertextual and textual analysis. The intertextual analysis is conducted both qualitatively and quantitatively. The qualitative analysis examines the level of dialogicality in reports from both media houses and how the reporters recontextualise the information in their reports. In addition, it will also study how both media houses frame the various voices in the discourse and investigate how other texts have been woven into the discourse intertextually. The quantitative analysis determines which voices have been included and excluded from the discourse. The textual analysis is conducted qualitatively and seeks to investigate how the reporters construct social reality through the representation of social actors and the use of transitivity. Findings from the qualitative intertextual analysis show that the mainstream media, as represented by The Star, endeavours to sustain the government’s hegemony by recontextualising and framing the various voices in the discourse. This is in contrast to Malaysiakini, which attempts to undermine the government’s hegemonic position. The quantitative analysis shows that government voices are the most highly represented in The Star compared to other voices, while opposition voices are the least represented. However, Malaysiakini offers a more balanced representation of voices in its reports. The textual analysis finds that both media houses attempt to construct a contrasting social reality through the representation of the various social actors in the discourse and the use of transitivity. The Star is supportive of the government’s decisions and hegemony, while Malaysiakini is more neutral on the issue. In conclusion, by comparing both media houses’ reports on the PPSMI issue over the period of three months, the researcher is able to determine the ideology of both The Star and Malaysiakini. The ideology of the mainstream media, as represented by The Star, is consistent with the dominant ideology of the ruling government, but the ideology of the alternative media, represented by Malaysiakini, does not support the government’s hegemonic position.